21.19. IDENTITY STAROIDS AND MULTIFUNCOIDS

371

Proof.

That

L /

GR id

Strd

A

[

n

]

if

L

k

=

for some

k

n

is obvious. It remains

to prove

L

∪{

(

k, X

t

Y

)

} ∈

GR id

Strd

A

[

n

]

L

∪{

(

k, X

)

} ∈

GR id

Strd

A

[

n

]

L

∪{

(

k, Y

)

} ∈

GR id

Strd

A

[

n

]

.

It is equivalent to

Z

l

i

n

\{

k

}

L

i

u

(

X

t

Y

)

6 A ⇔

Z

l

i

n

\{

k

}

L

i

u

X

6 A ∨

Z

l

i

n

\{

k

}

L

i

u

Y

6 A

.

Really,

Z

l

i

n

\{

k

}

L

i

u

(

X

t

Y

)

6 A ⇔

Z

l

i

n

\{

k

}

((

L

i

u

X

)

t

(

L

i

u

Y

))

Z

l

i

n

\{

k

}

L

i

u

X

t

Z

l

i

n

\{

k

}

L

i

u

Y

6 A ⇔

Z

l

i

n

\{

k

}

L

i

u

X

6 A ∨

Z

l

i

n

\{

k

}

L

i

u

Y

6 A

.

Proposition

1873

.

Let (

A

,

Z

) be a primary filtrator over a boolean lattice.

ID

Strd

A

[

n

]

is a completary staroid for every

A ∈

A

.

Proof.

?

A

is a free star by theorem

611

.

L

0

t

L

1

GR ID

Strd

A

[

n

]

⇔ ∀

i

n

: (

L

0

t

L

1

)

i

?

A ⇔ ∀

i

n

:

L

0

i

t

L

1

i

?

A ⇔

i

n

: (

L

0

i

?

A ∨

L

1

i

?

A

)

⇔ ∃

c

∈ {

0

,

1

}

n

i

n

:

L

c

(

i

)

i

?

A ⇔

c

∈ {

0

,

1

}

n

: (

λi

n

:

L

c

(

i

)

i

)

GR ID

Strd

A

[

n

]

.

Lemma

1874

.

X

GR id

Strd

A

[

n

]

Cor

0

d

A

i

n

X

i

6 A

for a join-closed filtrator

(

A

,

Z

) such that both

A

and

Z

are complete lattices, provided that

A ∈

A

.

Proof.

X

GR id

Strd

A

[

n

]

d

Z

i

n

X

i

6 A ⇔

Cor

0

d

A

i

n

X

i

6 A

(theorem

599

).

Conjecture

1875

.

id

Strd

A

[

n

]

is a completary staroid for every set-theoretic fil-

ter

A

.

Conjecture

1876

.

id

Strd

A

[

n

]

is a completary staroid if

A

is a filter on a set

and

n

is an index set.

21.19.4. Special case of sets and filters.

Proposition

1877

.

Z

n

X

GR id

Strd

a

[

n

]

⇔ ∀

A

a

:

Q

X

6

id

A

[

n

]

for every

filter

a

on a powerset and index set

n

.

Proof.

A

a

:

Y

X

6

id

A

[

n

]

⇔ ∀

A

a

:

\

i

n

X

i

A

6

=

∅ ⇔ ∀

A

a

:

Z

l

i

n

X

i

6

A

A

a

:

Z

l

i

n

X

i

6

A

A

Z

l

i

n

Z

X

i

6

A

a

Z

l

i

n

(

Z

n

X

)

i

6

A

a

⇔↑

Z

n

X

GR id

a

[

n

]

.